2012
DOI: 10.1093/carcin/bgs260
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of tobacco carcinogen-induced lung cancer in female mice using antiestrogens

Abstract: Increasing evidence shows that estrogens are involved in lung cancer proliferation and progression, and most human lung tumors express estrogen receptor β (ERβ) as well as aromatase. To determine if the aromatase inhibitor anastrozole prevents development of lung tumors induced by a tobacco carcinogen, alone or in combination with the ER antagonist fulvestrant, ovariectomized female mice received treatments with the tobacco carcinogen 4-(methylnitrosoamino)-1-(3-pyridyl)-1-butanone (NNK) along with daily suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(72 citation statements)
references
References 43 publications
5
67
0
Order By: Relevance
“…In human breast cancer, patients treated with anastrozole showed a reduction in Ki67 index, two months after the treatment onset [20]. In mouse lung cancer induced by tobacco carcinogen NNK, anastrozole also produce a decrease in the Ki67 cell proliferation index demonstrating the effectiveness of this medication in several cancer types [21]. Thus, our results encourage us to test this medication for GBM treatment in the human being.…”
Section: Discussionsupporting
confidence: 54%
“…In human breast cancer, patients treated with anastrozole showed a reduction in Ki67 index, two months after the treatment onset [20]. In mouse lung cancer induced by tobacco carcinogen NNK, anastrozole also produce a decrease in the Ki67 cell proliferation index demonstrating the effectiveness of this medication in several cancer types [21]. Thus, our results encourage us to test this medication for GBM treatment in the human being.…”
Section: Discussionsupporting
confidence: 54%
“…We showed that tissue aromatase is expressed in the lungs, especially in pulmonary macrophages [16]. The AI anastrozole and/or the anti-estrogen fulvestrant were administered as described and the published data showed that these agents, especially in combination, effectively inhibited NNK-induced lung adenoma formation by up to 75%, and also reduced the number of preneoplasias [16].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, CS was found to accelerate the production of the carcinogenic estrogenic metabolites 4-OHEs in the lungs (76), and the role that estrogen-metabolizing enzymes such as Cytochrome P450 1b1 (CYP1B1) may have in the enhanced female genderrelated susceptibility to tobacco has also been previously reported (75,81,82). The CS carcinogen nicotine-derived nitrosamine ketone (NNK) was shown to induce ERα via CYP1B1 activation (83), and anti-estrogens effectively inhibited NNK-induced murine lung carcinogenesis (84).…”
Section: Sex Differences In Lc Susceptibilitymentioning
confidence: 89%